Recent advancements and new perspectives in animal models for Neurocysticercosis immunopathogenesis. (July 2017) - Arora, N.; Tripathi, S.; Kumar, P.; Mondal, P.; Mishra, A.; Prasad, A.
SUMMARY: Neurocysticercosis (NCC), one of the most common parasitic diseases of the central nervous system, is caused by Taenia solium . This parasite involves two hosts, intermediate hosts (pig and human) and a definitive host (human) and has various stages in its complex life cycle (eggs, oncosphere, cysticerci and adult tapeworm). Hence, developing an animal model for T. solium that mimics its natural course of infection is quite challenging. We have reviewed here the animal models frequently used to study immunopathogenesis of cysticercosis and also discussed their usefulness for NCC studies. We found that researchers have used mice, rats, guinea pigs, dogs, cats and pigs as models for this disease with varying degrees of success. Mice and rats models have been utilized extensively for immunopathogenesis studies due to their relative ease of handling and abundance of commercially available reagents to study these small animal models. These models have provided some very exciting results for in‐depth understanding of the disease. Of late, the experimentally/naturally infected swine model is turning out to be the best animal model as the disease progression closely resembles human infection in pigs. However, handling large experimental animals has its own challenges and limitations.